Diferenciação tecnológica na agropecuária do nordeste brasileiro: uma análise comparativa entre semiárido e não semiárido - Machado, Bruno Ferreira (2024)
This study aims to identify technological differentiation in agricultural production among municipalities in the Semi-Arid and other regions of Northeast Brazil. To achieve this objective, the Metafrontier Production methodology proposed by Battese et al. (2004) and O'Donnell et al. (2008) was employed. The results confirm that the Semi-Arid and non-Semi-Arid regions do not share the same production technology, emphasizing the importance of public policies in reducing technological and productive disparities. Promising strategies include investments in workforce training, subsidized credit for modernization, and facilitating access to modern inputs. Furthermore, the results reveal that the presence of some municipalities in the MATOPIBA region, both in the semi-arid and non-semi-arid areas, has introduced a source of technological heterogeneity within each of the regions. This indicates the existence of a rich and complex technological landscape, transcending the duality between the semi-arid, characterized by subsistence agriculture, and the non-semi-arid, focused on commercial production and technological dynamism.